Beeswax waste improves the mycelial growth, fruiting body yield, and quality of oyster mushrooms (Pleurotus ostreatus) - Chunlei Pan; Chunge Sheng; Kang Wang; Yi Zhang; Chunguang Liu; Zhihao Zhang; Liang Tao; Yang Lv; Fuchao Gao (PeerJ)
Heilongjiang Province has the third largest bee population in China, producing over 2,000 tons of beeswax waste (BW) each year. Most of this BW is discarded or burned. Therefore, we urgently need to find sustainable applications of BW. Pleurotus ostreatus mushrooms, commonly referred to as oyster mushrooms, are cultivated for both food and medicine. The substrate used to grow P. ostreatus mushrooms often contains wheat bran as a nitrogen source. The goal of this study was to explore the feasibility of substituting this wheat bran with BW to cultivate P. ostreatus mushrooms. Five treatments were established, with BW making up 0%, 3%, 5%, 7%, and 9% of the total substrate, and the effects on the mycelial growth and development, biological efficiency (BE), and yield were evaluated along with changes in the chemical biomass composition of the fruiting bodies. Adding BW increased the number of days needed for primordia initiation and the number of days between flushes of P. ostreatus mushrooms. With increasing BW, the total fresh weight of P. ostreatus mushrooms first increased and then decreased. The 5% BW treatment resulted in the highest yield and biological efficiency (BE) of 1,478.96 ± 9.61 g bag−1 and 92.43 ± 0.60%, respectively, which exceeded the values of the control by 4.14% (control: 1,420.15 ± 9.53 g bag−1 and 88.76 ± 0.60%, respectively). The 5% BW treatment also resulted in the highest mushroom crude protein content (23.47 ± 0.18 g 100 g−1), which was 28.18% higher compared with the control (18.31 ± 0.05 g 100 g−1). The 9% BW treatment resulted in the highest crude polysaccharide content (10.33 ± 0.76 g 100 g−1), which was 2.42-fold that of the control (4.26 ± 0.30 g 100 g−1). This study suggests that BW could serve as an effective source of nitrogen to cultivate P. ostreatus. BW is a promising, cost-effective, and efficient additive to mushroom substrate, improving the yield and quality of P. ostreatus mushrooms while providing a sustainable use for an otherwise difficult to dispose of waste product.